HIV test-and-treat policy improves clinical outcomes in Zambian adults from Southern Province: a multicenter retrospective cohort study - Hamooya, Benson M.; Mutembo, Simon; Muyunda, Brian; Mweebo, Keith; Kancheya, Nzali; Sikazwe, Lyapa; Sakala, Morgan; Mvula, Johanzi; Kunda, Salazeh; Kabesha, Shem; Cheelo, Chilala; Fwemba, Isaac; et al. (Frontiers in Public Health, 2023)
Background: Globally, most countries have implemented a test-and-treat policy to reduce morbidity and mortality associated with HIV infection. However, the impact of this strategy has not been critically appraised in many settings including Zambia. We evaluated retention and clinical outcomes of adults enrolled on antiretroviral therapy (ART) and assessed the impact of the test-and-treat policy. Methods: We conducted a retrospective cohort study among 6,640 individuals who initiated ART between January 1 st , 2014 -July 31 st , 2016 (before test-and-treat cohort (BTT), n=2,991), and August 1 st , 2016 -October 1 st , 2020 (after test-and-treat cohort (ATT), n=3,649) in 12 districts of the Southern province. To assess factors associated with retention, we used logistic regression (xtlogit model). Results: The median age (interquartile range (IQR)) was 34.8 years (28.0, 42.1) and 60.2% (n=3,995) were females. The overall retention was 83.4% (95% confidence interval (CI) 82.6, 84.4) and it was significantly higher among ATT cohort, 90.6% vs. 74.8%, p<0.001. The reasons for attrition were higher BTT compared to ATT; stopped treatment (0.3 vs. 0.1%), transferred out (9.3 vs. 3.2%), lost to follow-up (13.5 vs. 5.9%) and death (1.4 vs. 0.2%). Retention in care was significantly associated with ATT cohort, increasing age and baseline body mass index (BMI), rural residence, and WHO stage 2; while non-retention was associated with never married, divorced and being in WHO staging 3.The retention rate and attrition factors improved ATT compared to BTT. Drivers of retention were test-and-treat policy, older age, high BMI, rural residence, marital status and WHO This is a provisional file, not the final typeset article stage 1. There is, therefore, a need for interventions targeting young people, urban residents, nonmarried, and those in the symptomatic WHO stages and with low BMI. Our findings highlight improved ART retention after the implementation of the test-and-treat policy.